Toward Interventions in Human Resources for Health in Ghana: Evidence for Health Workforce Planning and Results - Appiah-Denkyira, Ebenezer (World Bank, 2015)
This book was produced to support the policy dialogue on Human Resources for Health (HRH) in Ghana. Despite some recent successes, further improvements in health outcomes are in part hampered by the lack of skilled service providers, or human resources for health (HRH), particularly in rural areas, that prevent critical health services from being accessed and adequately delivered to those that need them most. To address the lack of information to guide the development of policies and programs on HRH, the book aims to paint a comprehensive picture on HRH, consolidating new and existing evidence on stock, distribution and performance of health workers to focus on the ?what?, as in ?What is the situation on HRH?? and the ?how?, as in ?How is this situation explained?? . The book highlights in particular new evidence on some of the underlying determinants impacting stock, distribution and performance of health workers in Ghana, including health worker production and attrition, management and accountability structures, the capacity of health training institutions, and health worker compensation. As is made clear, any potential policies to improve the situation on HRH need to be well targeted, and take into account some of the fiscal and political challenges that are specific to the health labor market in Ghana. The data and findings presented in this book are the result of extended and close collaboration between the Ghana Ministry of Health, and the World Bank?s Africa Region Technical Team on HRH and will provide a better basis for Ghanaian decision makers and external partners to dialogue on HRH and related policies, resulting in concrete HRH actions. More broadly, it will be of interest to all those working to improve Human Resources for Health in Africa and beyond.